Organic Fertilizer Production from Corn Litter Waste Using Micro bacteria - Manshurin, Abi; Nurazizah, Kaylha Salsabilla; Putra, Aditya Permana; Putri, Arifa Lutfiya Amanda; Haris, Amnan; Fibriana, Fidia; Febriyanto, Hendra (ORGANISMS: JOURNAL OF BIOSCIENCES, 2025)
The use of organic fertilizers is considered to be beneficial by farmers such as increasing land productivity. Corn farming contributes the highest agricultural waste in Indonesia, such as stem litter, leaves and husks. This waste has the potential to be used as organic fertilizer because based on research it contains many nutrients in it. This study aims to evaluate the effectiveness of EM4-based microbial treatment in accelerating the composting of corn litter waste through observational qualitative analysis. The results of this study indicate that the addition of microorganisms can shorten the time to make organic fertilizer. On the 6th day, the corn litter waste sample that had been given EM4 had shown the appropriate criteria for organic fertilizer in the form of a neutral pH concentration of 6.5 and did not have a disturbing odor and a texture that was no longer stiff. These findings suggest that EM4 can be used to accelerate composting of corn waste into high-quality organic fertilizer, potentially supporting sustainable agriculture.